Information literacy skills instruction in Spanish university libraries of economics - Marcos-Treceño, María-Jesús (Revista General de Información y Documentación, 2018)
Information literacy instruction in Spain by librarians in Economics, Business Administration, Accounting, Finance, Banking, and Insurance is analyzed. The data was collected through a survey and assesses information literacy skills and knowledge of library resources and services. Positive aspects and shortcomings are identified and recommendations are given for improvement. Also, specific student traits and informational competencies are explored for economics students. Among other conclusions, there is the delay in the inclusion of digital skills and a need to collaborate with other university actors.
Keywords: Information literacy skills; Digital skills; Information literacy; University libraries; Economics; Business; Teaching programs; Survey; Spain.